Application of biosecurity in small scale pig farm in Hung Yen and Nghe An provinces - Pham Hong Ngan; Duong Van Nhiem; Vu Thi Thu Tra; Ngo Minh Ha; Dinh Phuong Nam; Unger, Fred (2016)
A survey on application of biosecurity in small scale pig farm in Hung Yen and Nghe An was carried out from March to December, 2014. Sixty household farms were selected randomly from the list of the farms that participated in the survey in 2013 in two provinces. Information on biosecurity measures, farm management, working and feed storage conditions were collected through the checklist survey sheets that were carried out for one time in every 2 weeks. The surveyed results showed that control of the visitor was not applied in most of the farms (69.7%), disinfection mattresses were not installed and maintained (54.0%), the farm workers usually did not wear protective clothes and boots during working time (81.2%), litter were not provided for the piglets (88.8%) and lack of heat sources (74.1%) during the cold period, water was not available at all times and in all barns (48.0%), feed was not properly covered and stored, therefore feed was affected by yeast-moisture (49.4%), rodent/pest (47.9%). The observed gaps in farm management and biosecurity practice will be addressed in the coming intervention phase.